ACTUAL PROBLEMS OF DENTISTRY (Лучшие интеллектуальные исследования, 2025)
Abstract. Today, the population, including cerebral palsy it is important to conduct scientific research on the optimization of measures for the treatment and prevention of caries in children, to study the spread of these diseases by world scientists in order to approach this problem in a scientifically based manner.